Memory wars and minority rights - Pirker, Jürgen (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2021)
Described as "the age of extremes" by historian Eric Hobsbawm, the 20th century was defined by heavily-contested borders and identities in Central Europe: politically, culturally, socially, and intellectually. With the end of World War I, communities found themselves in new nation- states, and the politics of assimilation and relations between minorities and their kinstates created tensions that continue to reverberate today. Using the Slovene minority in Austria as a case study, the article provides insight into two international projects that involve civil society actors in the field of memory politics and young people and their attitudes towards history and minorities. In drawing lessons from these initiatives dealing with troubled pasts to counteract current forms of exclusive identity politics, the article proposes that effective minority protection depends on a conductive social environment that allows for the reflection of opposing narratives stemming from ethnic conflict and acknowledges diversity as enrichment.
Keywords: Avstrija; Avstrijska Koroška; dialog; etnični spor; plebiscit; politika spomina